Let's face it, writing is hell : challenges of being a fiction writer in Bhutan ([Thimphu] : [Royal Thimphu College], 2017)
Spiral-bound xerographic copy.
Student research project for BA, Political Science (Capstone Project):(2017).
Includes bibliographical references.
Keywords: Authors, Bhutanese; Bhutanese fiction (English).; Capstone Project